Analisis dan Desain Klasifikasi Produk sebagai Dampak Covid 19 pada Industri Furnitur - Salim, Nazmi; Taufik, (JURNAL AGROINDUSTRI HALAL, 2023)
The furniture industry is one of the industries affected by Covid-19 which has caused a change in inventory management. The purpose of this study is to analyze changes in product classification based on the ABC-XYZ analysis for 2019-2022. The results of the study show that there has been a change in product classification from 2019-2022. The Covid-19 pandemic has resulted in a decrease in demand for wardrobe products at PT XYZ. A CV value above 30% indicates that the product demand is very difficult to predict, especially during the Covid-19 pandemic. Demand for 2022 has improved compared to the previous two years. The results of the ABC-XYZ classification show that companies need to exercise good control over demand for class AZ even though they still have a large CV value. A CV value that is too large can be caused by the data forming seasonal data, even though the furniture product is not a seasonal product. This happened because there were sales that fell and had an impact on the company's operations, especially product inventory. There are seven products that are in class AZ and are priority products that need inventory control compared to other classes.